Changes in mental health levels among Chinese athletes from 1995 to 2023 - Xi, Yue; Liu, Fengbo; Yang, Jian (Frontiers in Psychology, 2024)
To understand the trend of mental health levels among Chinese athletes over the years, a total of 306 articles were accumulated from September to November 2022 by selecting literature from databases such as CNKI, Wanfang, and Weipu that measured the mental health of Chinese athletes using the Symptom Checklist-90 (SCL-90). Based on the screening criteria, 28 articles(N=4227) were finally included. A cross-sectional historical meta-analysis of these 28 studies using the SCL-90 between 1995 and 2023 was conducted. Based on cross-sectional historical meta-analysis methods, specific statistical methods, such as correlation and regression analyses, were used to examine trends over time in the scores of the nine psychological problem factors measured by the athletes in the studies, as well as athlete type and gender differences. It was found that athletes' scores on the depression, hostility, terror, and paranoia factors gradually increased with the change of era, and the explanation rate of the variation of each factor by era ranged from 18.8% to 27.2%; during the period from 1995 to 2023, the mental health of athletes in China gradually deteriorated on the factors of depression, hostility, and terror, and the rate of change was rapid, with a medium to large magnitude (0.28-0.42); the scores of female athletes on the depression factor and psychotic factor scores showed a significant upward trend, while male mental health scores for each factor did not improve significantly over the years; college athletes' scores on the depression factor, anxiety factor, hostility factor, horror factor, paranoia factor, and psychoticism factor showed an upward trend as the years changed. In summary, the mental health level of Chinese athletes has decreased over the past 28 years.